PENGEMBANGAN MODEL BUKU PELAJARAN BAHASA INDONESIA BERBASIS PEMBELAJARAN KONTEKSTUAL - Suryaman, Maman (Diksi, 2008)
This article is about a research with the objective of discovering a modelfor a course book based on contextual instruction for junior high school classes ofIndonesian. To achieve the objective, in the first phase of the research, that is, in thefirst year, 2007, the research had the specific objective of discoveringmanifestations of contextual instruction to serve as starting points in developingthe model. The research subjects consisted of (1) class instruction, (2) students,and (3) course books of Indonesian.The research results indicated the following. (1) When a constructivestrategy is used, the contextual manifestations are, among others, simpleformulations of objectives, uses of operational verbs, the appearance of themes,the mapping of new experiences, an appropriateness of the strategy and methodfrom the point of objectives and learners' characteristics, and language suitability.(2) When an inquiry strategy is used, the manifestations are, among others, a matchbetween objectives and thematic basic competency indicators, consideration oflearners' needs, appropriate selection of media, appropriateness of the strategy andmethod from the point of learners' needs, hypothesis confirmation or testing, andgain of new experience. (3) When a question-and-answer strategy is used, themanifestations are, among others, apperception, questions and answers,encouragement through questions, and asking resource persons questions. (4)When a modeling strategy is used, the manifestations consist of imitation, givingexamples, making use of examples, and variety of examples. (5) When a learningcommunitystrategy is used, the manifestations consist of the discovery of newexperience, problem-solving through group work, development of selfdependenceas well as collaborative work, communication of learning results toothers, communication of works to others, and ethical formation. (6) When anauthentic-assessment strategy is used, the manifestations consist of variety inmethod of assessment, presentation of work, and work performance. (7) When areflection strategy is used, the manifestations consist of linking learning resultswith benefits for learners, self-development, expansion of experience, pursuit ofmeaning, creation of a feeling of pleasure, support of what one dreams to achieve,and creation of motivation. (8) The anatomy of the course book consists of (a) theintroduction, containing the title of the book, preface, table of contents, andorganization of content, (b) the content, containing the material, materialpresentation, and strategy of presentation, and (c) the conclusion, containing theevaluation, reflection, bibliography, index, and relevant answer keys.Keywords: course book, contextual manifestations and strategies